Study The Waveform Analysis of Interconnect Performance For Future Vlsi Design - Singh, Devender Pal (My University, 2013)
Propagation delay plays an important role in the performance of a chip. But aggressive technology scaling in VLSI field results an increase in resistance of copper interconnect which causes increase in propagation delay. Many researchers show that carbon nanotubes are the best promising candidates for next generation of VLSI interconnect. Carbon nanotubes are preferred over copper interconnect due to their high current carrying capacity and high thermal conductivity. In this dissertation analytical expression of the output waveform of an SWCNT bundle interconnect and coupled interconnects are presented at 32 nm technology node. Alpha power law model is used to derive current expression for driver transistor and results are compared with existing copper interconnect at same technology node and frequency. A good agreement between analytical model and SPICE simulation model is observed. The effect of various parameters such as interconnect length, driver size and number of repeaters on propagation delay has been analyzed. The crosstalk induced waveform at victim output has been derived and compared with SPICE simulation results.
MT, ECED
Keywords: VLSI Interconnect; CNT; Propagation delay